A method to rapidly build complex three-dimensional models of rock-filled concrete. (June 2023) - Liang, YiHui; Zou, Shuang; Xie, CaiJin
Highlights: The use of point clouds significantly reduces the time spent on model generation. The parameter space is the basis for building complex models. The model of concrete built by numerical methods can also have a parameter space. The interfacial transition zone can be generated by modifying the parameter space. Models with a higher rockfill ratio can be generated using the compacting method. Abstract: There are four critical problems in the numerical modeling of rock-filled concrete: the generation of a high rockfill ratio model, the formation of a rock skeleton, the generation of the interfacial transition zone, and the operability of the model after generation. In this paper, we propose a numerical method called the parameter space reconstruction method, which perfectly solves these problems based on the improving efficiency of model generation. Firstly, the rocks are placed in the expanded space to construct the initial parameter space. Secondly, the falling and compacting simulations are performed on the placed rocks to form a model with a rock skeleton and a high rockfill ratio. Thirdly, the simulation results are used to reconstruct the initial parameter space. Since the reconstructed parameter space is obtained by correcting the initial parameter space using the falling and compacting simulation results, it is still operable. Finally, the interfacial transition zone can be generated by continuing to modify the reconfigured parameter space. To verify the accuracy of this method, we perform uniaxial compressive strength simulations on the model generated using this method, and the simulation results show a good agreement with the experimental results.